2015
DOI: 10.4236/ns.2015.74022
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Annual Effective Dose Due to Ingestion of Natural Radionuclides in Cattle in Tin Mining Areas of Jos Plateau, Nigeria: Are Large Mammals Really Affected?

Abstract: We have read with great interest the paper which was published in Natural Science, 2014 issue number 6 titled "Estimation of annual effective dose due to ingestion of natural radionuclides in cattle in tin mining area of Jos Plateau, Nigeria" [1]. The paper motivated us to use state-of-the-art computational technique to investigate the risks of the tin mining activity in Jos-Plateau, Nigeria on large mammals (e.g. cattle). The Tier 2 Erica Tool assessment was used to estimate the total dose rate and risk quoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The study reported high activity concentration of 40 K in the studied cattle organs. However, there were limitations of the study design and presentation that raise questions concerning the utility of the findings (Aliyu et al 2015a). For instance, the very small sample size (only five cows) and limited controls likely biased the results of the study.…”
Section: Resultsmentioning
confidence: 99%
“…The study reported high activity concentration of 40 K in the studied cattle organs. However, there were limitations of the study design and presentation that raise questions concerning the utility of the findings (Aliyu et al 2015a). For instance, the very small sample size (only five cows) and limited controls likely biased the results of the study.…”
Section: Resultsmentioning
confidence: 99%
“…Venetia mines (South Africa) and Orapa mines (Botswana), and iron ore extraction in Guinea, phosphate mines (Togo), Uranium mines (Niger), etc. In many cases, these activities have resulted in negative environmental impacts including polluted freshwater resources that have become toxic and unsafe for drinking and fishing, as well as pollution of wetlands and soils rendering them unsafe for agriculture (Sracek et al, 2012;Aliyu et al, 2015). This is particularly evident in the severe impact of oil spills from drilling activities in the Niger Delta (Nigeria) on the livelihoods of local communities.…”
Section: Mining and Drilling As A Disturbance Regimementioning
confidence: 99%